1998
DOI: 10.1094/cchem.1998.75.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification of a Water‐Extractable Rye (Secale cereale) Protein Capable of Improving the Quality of Wheat Bread

Abstract: Rye water‐soluble extracts contain a protein fraction that, when added at low concentrations to a straight‐dough breadmaking recipe, significantly increased bread volume. Enrichment of the active component is possible by anion‐exchange fractionation with diethylaminoethyl‐cellulose (DEAE), by ammonium sulfate precipitation, or by using rye bran or shorts milling fractions as the starting material. The active material was not bound to DEAE‐cellulose. With ammonium sulfate precipitation, the fractions obtained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Weipert et al () reported that flours from rye cultivars exhibiting high total arabinoxylan content and a high proportion of WEAX yielded rye breads (using a sourdough formula) of good quality. Similarly, including WEAX from rye in a wheat bread formulation improved baking quality ( ). On the basis of these studies, it could be concluded that the concentration of WEAX is an important factor determining the baking quality of rye and that higher levels of WEAX would be associated with superior baking quality.…”
Section: Introductionmentioning
confidence: 99%
“…Weipert et al () reported that flours from rye cultivars exhibiting high total arabinoxylan content and a high proportion of WEAX yielded rye breads (using a sourdough formula) of good quality. Similarly, including WEAX from rye in a wheat bread formulation improved baking quality ( ). On the basis of these studies, it could be concluded that the concentration of WEAX is an important factor determining the baking quality of rye and that higher levels of WEAX would be associated with superior baking quality.…”
Section: Introductionmentioning
confidence: 99%